CODE STROKE ALERT—Concept and Development of a Novel Open-Source Platform to Streamline Acute Stroke Management - Seah, Huey Ming; Burney, Moe; Phan, Michael; Shell, Daniel; Wu, Jamin; Zhou, Kevin; Brooks, Owen; Coulton, Bronwyn; Maingard, Julian; Tang, Jennifer; Yazdabadi, Gohar; Tahayori, Bahman; et al. (Frontiers in Neurology, 2019)
Introduction Effective, time-critical intervention in acute stroke is crucial to mitigate mortality rate and morbidity, but delivery of reperfusion treatments is often hampered by pre-, in- or inter-hospital system level delays. Disjointed, repetitive and inefficient communication is a consistent contributor to avoidable treatment delay. In the era of rapid reperfusion therapy for ischaemic stroke, there is a need for a communication system to synchronise the flow of clinical information across the entire stroke journey. Material/Methods A multi-disciplinary development team designed an electronic communications platform, integrated between web browsers and a mobile application, to link all relevant members of the stroke treatment pathway. The platform uses tiered notifications, geotagging, incorporates multiple clinical score calculators, and is compliant with security regulations. The system safely saves relevant information for audit and research. Results Code Stroke Alert is a platform that can be accessed by emergency medical services (EMS) and hospital staff, coordinating the flow of information during acute stroke care, reducing duplication and error in clinical information handover. Through acceleration of the numerous and complex logistical processes required to achieve reperfusion, Code Stroke Alert offers substantial potential benefit to improve patient outcome. Electronic data logs provide an auditable trail of relevant quality improvement metrics, facilitating quality improvement and research. Discussion Code Stroke Alert will be freely available to health networks globally. The open-source nature of the software offers valuable potential for future development of plug-ins and add-ons, based on individual institutional needs. Prospective, multi-site implementation and measurement of clinical impact are underway.